‘Too male, too pale, too stale’: a qualitative exploration of student experiences of gender bias within medical education - Megan E L Brown; Gabrielle M Finn; George E G Hunt; Ffion Hughes (BMJ Open)
Objective To explore medical student perceptions and experiences of gender bias within medical education.Setting Gender bias—‘prejudiced actions or thoughts based on the perception that women are not equal to men’—is a widespread issue. Within medicine, the pay gap, under-representation of women in senior roles and sexual harassment are among the most concerning issues demonstrating its presence and impact. While research investigating experiences of clinicians is gaining traction, investigation of medical students’ experiences is lacking. This qualitative study analyses medical students’ experiences of gender bias within their education to discern any patterns to this bias. Illuminating the current state of medical education gender bias will hopefully highlight areas in which student experience could be improved. Constructivist thematic analysis was used to analyse data, informed by William’s patterns of gender bias, intersectional feminism and communities of practice theory.Participants Thirty-two medical students from multiple UK medical schools participated in individual interviews. Nine faculty members were also interviewed to triangulate data.Results Gender bias has an overt presence during medical student education, manifesting in line with William’s patterns of bias, impacting career aspirations. Physical environments serve to manifest organisational values, sending implicit messages regarding who is most welcome—currently, this imagery remains ‘too male, too pale…too stale’. Existing gender initiatives require careful scrutiny, as this work identifies the superficial application of positive action, and a failure to affect meaningful change.Conclusions Despite progress having been made regarding overt gender discrimination, implicit bias persists, with existing positive action inadequate in promoting the advancement of women. Institutions should mandate participation in implicit bias education programmes for all staff and must strive to revise the imagery within physical environments to better represent society. Gender initiatives, like Athena Scientific Women’s Academic Network, also require large-scale evaluation regarding their impact, which this work found to be lacking.